Effect of the application of abscisic acid and ethephon on the quality of Merlot grapes grown in Serra Gaúcha, South Brazil - Susin, Eliane (2022)
Currently, viticulture is using plant growth regulators as an alternative to increasing grape and must quality for vinification. This work aimed to evaluate the effect of different doses of abscisic acid and ethephon on the quality of Merlot grapes. The plant growth regulators were applied isolated and combined, on the stages of veraison and 15 days before harvest (DBH). The parameters of mass and berry diameter, soluble solids content, titratable acidity, must pH, phenolic compounds, and total anthocyanin contents. The results showed that the application of ethephon at the dose of 200 mg∙L-1 on veraison caused an earlier bunch threshing, an increased berry peel sensibility, and rupture ripening grapes, in both productive cycles. The use of abscisic acid at the dose of 600 mg∙L-1 helped increase the soluble solids content of the grapes, however, a strong influence of the climatic conditions was observed on the effect of the plant growth regulations on Merlot grapes.